Research on system of ultra-flat carrying robot based on improved PSO algorithm - Zhu, Jinghao; Wu, Jun; Chen, Zhongxiang; Cao, Libo; Yang, Minghai; Xu, Wu (Frontiers in Neurorobotics, 2023)
The ultra-flat carrying robot (UCR) is used to carry soft targets for functional safety road tests of intelligent driving vehicles, and should have superior control performance. For the sake of analyzing and upgrading the motion control performance of the ultra-flat carrying robot, this paper develops the mathematical model of its motion control system on the basis of the test data and the system identification method. Aiming at ameliorating the defects of the standard particle swarm optimization (PSO) algorithm, namely low accuracy, being susceptible to being caught in a local optimum and slow convergence when dealing with parameter identification problems of complex systems, this paper proposes a refined PSO algorithm (IWCNS-PSO) with inertia weight cosine adjustment and introduction of natural selection principle, and verifies the superiority of the algorithm by test functions. Based on the IWCNS-PSO algorithm, the identification of transfer functions in motion control system of the ultra-flat carrying robot is completed. In comparison with the identification results of standard PSO and LDIW (Linear Decreasing Inertia Weight) -PSO, it indicates that the IWCNS-PSO has the optimal performance with the number of iterations it takes to reach convergence being only 95 and the fitness value being only 0.117. The interactive simulation model is constructed in MATLAB/Simulink, and the critical proportioning method and the IWCNS-PSO algorithm are employed respectively to complete the tuning and optimization of the PI controller parameters. The results of simulation indicate that the PI parameters optimized by the IWCNS-PSO algorithm reduce the adjustment time to 7.99s and the overshoot to 13.41% of the system, and the system has been significantly improved with regard to the control performance, which basically meets the performance requirements of speed, stability and accuracy for the control system. In conclusion, the IWCNS-PSO algorithm presented in this paper represents an efficient system identification method, as well as system optimization method.